Diverse Pedagogical Approaches to Experiential Learning Multidisciplinary Case Studies, Reflections, and Strategies - Lovett, Karen; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Palgrave Macmillan, 2020)
This edited collection offers a unique multidisciplinary perspective into the many factors that go into designing, facilitating, expanding, and assessing experiential learning (EL) from the perspective of faculty and staff educators. The editor and contributors bring decades of expertise with different forms of EL, including community-engaged learning, education abroad, internships, and more. Chapters offer case studies and reflections which highlight personal experiences and anecdotes which illuminate the realities of experiential teaching and learning. Through these stories and narratives, readers may better understand what doing EL entails on an everyday basis$1 (Bboth on a local and global scale$1 (Band learn how to enhance support and resources for experiential educators on college and university campuses.s
1. Introduction: Listening and Learning from Experiential Learning Educators -- 2. When Students Write for Money: Reflections on a Decade of Teaching Grant Writing -- 3. Intergenerational Engagement through Experiential Learning -- 4. Museums and Mud: An Experiential Undergraduate Geology Course for Preservice Teachers -- 5. Forming Engineers for the Common Good -- 6. The Processes of Reciprocity and Reflection in Service-Learning Pedagogy -- 7. Experiential Learning in Sustainability: Opportunities, Building Partnerships, and Student Engagement -- 8. We Are All Students: The Moral Courage Project as a Model for Transdisciplinary Experiential Learning -- 9. Dinner in the Desert Kitchen: Reflections on Experiential Learning through Food, Art and Social Practice -- 10. Critical Cosmopolitan Citizens: Experiential Engagement with Local Immigrant and Refugee Communities -- 11. Writing the History of the Dayton Arcade: Experiential Learning through Immersion, Collaboration, and Service -- 12. Power, Access, and Policy: Reflections on the Women's Center Internship Program -- 13. Beyond Skepticism or Compassion: A Critical Pedagogy of Gender-Based Violence -- 14. Performing Arts in the Service of Others: The Common Good Players and Experiential Learning in Social Justice Theatre -- 15. Student Employment for the Real World: Experiential Learning and Student Development -- 16. Experiential Learning and Education Abroad: Examining the Experiences of Students in the Semester Abroad and Intercultural Learning Program -- 17. Afterword: Learning, With Consequence.-.
Keywords: Higher education; Lifelong learning; Adult education; Professional education; Vocational education; Teaching; Applied sociology; Higher Education; Lifelong Learning/Adult Education; Professional & Vocational Education; Teaching and Teacher Education; Social/Human Development Studies